Gallium vacancies role in hydrogen storage of single-crystalline GaN hexagonal micro-sheets. (7th February 2020) - Nabi, Ghulam; Kamran, Muhammad Arshad; Alharbi, Thamer; Rafique, Muhammad; Tahir, M. Bilal; Hussain, Sajad; Khalid, N.R.; Iqbal, Tahir; Shakil, Muhammad; Cao, Chuanbao
Abstract: Hydrogen as a vehicular fuel has attracted extensive attention. However, the challenge of its storage extremely confined its applications. Current researchers are mostly focused on the development of porous nanomaterials having large specific surface areas for improving the gravimetric densities, which undoubtedly restrain the volumetric densities of hydrogen storage. Here, hexagonal GaN micro–sheets are reported for hydrogen storage. Compared with the porous nanostructures, the highly crystalline structure micro–sheets ensure the volumetric density of GaN. The adsorption and the insertion of the hydrogen atoms into the crystal lattice and Ga vacancies result in reversible gravimetric densities. GaN micro–sheets absorption results are comparable to porous nanomaterials and higher than many oxide and nitride materials. Furthermore, the role of Ga vacancies has been correlated with morphology and the absorption mechanism. Graphical abstract: Image 1 Highlights: Role of Gallium vacancies in GaN hexagonal micro-sheets for hydrogen storage. Two‒dimensional (2D) diffusion model of kinetics modes best fitted on GaN micro-sheets. Growth mechanism of two-dimensional (2D) micro-sheets is described. Yellow band emission (Ga vacancies) at 553 nm is crucial for Hydrogen Storing.